Promoting Spatial Partnership and Community Perception for the Preservation of Orang Kayo Hitam Grand Forest Park (GFP) in Jambi Province, Indonesia - Rosyani Rosyani; Fuad Mukhlis; Fazriyas Fazriyas; Neliyati Neliyati; Napitupulu Napitupulu; Addion Nizori; Heiko Faust (Faculty of Geography, Universitas Gadjah Mada, 2023)
The Orang Kayo Hitam Grand Forest Park is located in Jambi Province, Indonesia, and is currently threatened by illegal logging and natural fire forest that has burned 7,984.78 hectares. Therefore, this research aims to improve community perceptions of the conservation function of the Orang Kayo Hitam. This can be achieved by providing conservation books on the Orang Kayo Hitam to the community, creating a demonstration video, and increasing community income through a partnership pattern by planting in utilization zones. The non-parametric statistical difference T-test was used, which involved a survey and training approach on 93 households living near the Grand Forest Park. This method was used to assess changes in the perception of the community after reading books, watching videos, and collaborating on counseling. The results showed that the perception of the community changed significantly after receiving knowledge from books and watching videos about the Grand Forest Park. There was also a shift in public perception regarding the use of the conservation zone at the Grand Forest Park location via collaboration counseling.